(untitled) (Texas Journal of Engineering and Technology, 2022)
Studies of the contamination of lubricating oils during operation in hot climates and high dustiness of the air show that lubricants are intensively contaminated with mechanical impurities, water, fuel and organic products, which leads to premature aging of the oil. During operation, engine components and parts are contaminated with various deposits. The process of sediment formation is associated with thermo-oxidative transformations of incomplete combustion products of fuel and oil components. These transformations occur both in the volume of oil and in its thin layer on a heated metal surface.